Steady Flow Analysis Performed for Flood Inundation Mapping Using HEC-RAS - Narahari M.; Rawal N.R.; Soni P. (My University, 2025)
Floods are a serious threat to human lives and property, with causes ranging from heavy rainfall to human-induced land-use changes and resulting hydrological consequences. In particular, the northern regions of India, where many rivers originate, face a prominent flood problem. Complex hydrological conditions make Prayagraj's Sangam region vulnerable to monsoon flooding. To aid in flood management and prevention efforts, this study employed the HEC-RAS model to conduct the steady flow analysis and generate flood maps for the area. Through a hydraulic model of a small catchment where the Ganga and Yamuna Rivers converge, the study identified flood-prone areas and assessed flood risk. The findings revealed that the Sangam region is highly vulnerable to flooding, with several areas at risk of inundation during the monsoon season. Notably, the study determined that urban areas would experience inundations of 58.57, 138.26, and 245.24 km2 for minimum, average, and maximum flood discharges, respectively. However, when considering a 10% higher maximum flood discharge as an extreme discharge, the affected area expanded to 353.69 km2. These flood maps serve as valuable tools for developing effective flood management strategies to mitigate the impact of flooding in the region. Moreover, the study underscores the significance of employing advanced models like HEC-RAS to analyze complex hydrological conditions, evaluate flood risk, and estimate the extent of inundation. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2025.